2017
DOI: 10.5312/wjo.v8.i9.726
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis action alliance consensus opinion - best practice features of anterior cruciate ligament and lower limb injury prevention programs

Abstract: AIMTo identify best practice features of an anterior cruciate ligament (ACL) and lower limb injury prevention programs (IPPs) to reduce osteoarthritis (OA).METHODSThis consensus statement started with us performing a systematic literature search for all relevant articles from 1960 through January 2017 in PubMed, Web of Science and CINAHL. The search strategy combined the Medical Subject Heading (MeSH) and keywords for terms: (1) ACL OR “knee injury” OR “anterior cruciate ligament”; (2) “prevention and control”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…However, they do not need to be overly time-intensive and can be integrated into a pre-existing warm-up or conditioning routine 4. Several injury and athletic organisations, including the National Athletic Trainers’ Association, the Academy of Orthopaedic Physical Therapy, the American Academy of Sports Physical Therapy, the Osteoarthritis Action Alliance, the American College of Sports Medicine and the International Olympic Committee, support and offer guidance on the use of injury prevention programmes to prevent knee injuries 4 19–22…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not need to be overly time-intensive and can be integrated into a pre-existing warm-up or conditioning routine 4. Several injury and athletic organisations, including the National Athletic Trainers’ Association, the Academy of Orthopaedic Physical Therapy, the American Academy of Sports Physical Therapy, the Osteoarthritis Action Alliance, the American College of Sports Medicine and the International Olympic Committee, support and offer guidance on the use of injury prevention programmes to prevent knee injuries 4 19–22…”
Section: Introductionmentioning
confidence: 99%
“…Although these improvements were not different than those from a warmup of the coaches' choosing, PTP use at this young age may be critical for building buy-in and acceptance of these types of warmup strategies given that the benefits of PTPs in adolescence for reducing injury risk are clearly established. [27][28][29] Coaches represent the best option for consistent, longterm use of PTPs, particularly at the youth level; however, high program complexity can be a barrier to implementation, 30 and coaches have reported that knowing how to give adequate feedback to athletes on injury-prevention techniques is a challenge. 31 Motor learning can be affected by the type of feedback provided, which can differ based on the focus of attention (eg, internal or external) and complexity.…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, there is a need to identify strategies to help mitigate the increased risk for radiographic knee OA in individuals engaged in heavy manual work. These may include strengthening exercises, injury prevention programmes, controlling ergonomic hazards, knee braces or weight loss 27–31. Future large prospective studies of people in high occupational work-related physical activity levels to evaluate for specific work-related tasks could be used to develop and refine preventative measures.…”
Section: Discussionmentioning
confidence: 99%